1969
DOI: 10.1111/j.1432-1033.1969.tb00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Peroxide-Inactivation of the Sulphydryl Enzyme Glyceraldehyde-3-Phosphate Dehydrogenase

Abstract: The inactivation of glyceraldehyde-3-phosphate dehydrogenase by hydrogen peroxide has (a) I n the absence of catalysts been investigated. The reaction obeyed two rate equations : did not oxidize the "essential" sulphydryl groups of the enzyme to disulphide, but to sulphenic acid residues. Peroxide-inactivated glyceraldehyde-3-phosphate dehydrogenase could be fully reactivated and sulphydryl oxidation fully reversed if the enzyme was treated immediately with excess small thiol. The reversibility of inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 23 publications
(9 reference statements)
5
94
1
Order By: Relevance
“…The protein undergoes S nitrosylation by NO (22,40), NAD ϩ covalent linkage upon S nitrosylation (40), nitroalkylation by nitrated fatty acids (3), S glutathionylation by glutathione or even by NO (39), and extensive oxidation by peroxynitrite or H 2 O 2 (33,53). Among these modifications, S glutathionylation, the formation of mixed disulfides between glutathione and the cysteine of some proteins, has attracted great interest, as it has recently emerged as a potential mechanism for the regulation of signaling and metabolic pathways under both physiological and pathological conditions (13,36).…”
Section: Discussionmentioning
confidence: 99%
“…The protein undergoes S nitrosylation by NO (22,40), NAD ϩ covalent linkage upon S nitrosylation (40), nitroalkylation by nitrated fatty acids (3), S glutathionylation by glutathione or even by NO (39), and extensive oxidation by peroxynitrite or H 2 O 2 (33,53). Among these modifications, S glutathionylation, the formation of mixed disulfides between glutathione and the cysteine of some proteins, has attracted great interest, as it has recently emerged as a potential mechanism for the regulation of signaling and metabolic pathways under both physiological and pathological conditions (13,36).…”
Section: Discussionmentioning
confidence: 99%
“…For phosphoglycerate kinase immobilization, 20 mg CNBr/ml gel were used. Preparation of immobilized monomeric and dimeric forms of yeast glyceraldehyde-3-phosphate dehydrogenase was as previously described [5, 121. The inactivation of the matrix-bound monomeric species by H 2 0 2 was carried out following the method of Little and O'Brien [13]. Immobilized enzyme was washed with 50 vol.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of cysteic acid in native transcortin cannot be assumed since that degree of oxidation cannot be reversed by DTT; the question then arises as to the presence of sulphenic (-SOH) or sulphinic (-SOzH) acid which can be reduced to thiol [ 151. It has been suggested that sulphenic acids, unlike disulphides, may be reduced to thiols by sodium arsenite, a very mild reductant [ 16,171. The effects of arsenite and of another mild reductant, sodium ascorbate, were therefore studied.…”
Section: Nature Of the Blocking Agent On The Available Sulphydryl Groupmentioning
confidence: 99%